2019
DOI: 10.1186/s13104-019-4125-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of self care practices among hypertensive patients at Jimma University Specialized Hospital, Southwest Ethiopia: cross-sectional study

Abstract: Objective Hypertension is a major risk factor and precursor of myocardial infarction, chronic kidney disease, heart failure and premature death. These vascular events increased costs of hypertension management. Self-care Practices were recommended to control blood pressure among hypertensive patients. Therefore, the objective of this study is to assess predictors of self-care practices among hypertensive patients at Jimma University Specialized Hospital. Results A 341-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 27 publications
5
32
1
7
Order By: Relevance
“…This study revealed that 57.5% of patients adhered to medication which was consistent with the results of a study done in North Carolina, 58.6%. 38 However, the finding was lower than the results of a study conducted in Jimma, 61.9% 31 , and Addis Ababa, 69.2%. 29 Compared to the results of a study done in southern India, 36.1%, 42 the finding in our study was higher.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…This study revealed that 57.5% of patients adhered to medication which was consistent with the results of a study done in North Carolina, 58.6%. 38 However, the finding was lower than the results of a study conducted in Jimma, 61.9% 31 , and Addis Ababa, 69.2%. 29 Compared to the results of a study done in southern India, 36.1%, 42 the finding in our study was higher.…”
Section: Discussioncontrasting
confidence: 58%
“…Pretested structured questionnaires adapted from validated scales and published literature [27][28][29][30][31][32][33][34][35][36][37][38] were used to collect data from participants. The tool contains sociodemographic characteristics (sex, age, religion, marital status, education, main occupation, and residence area and wealth index), health profiles of the patients (comorbidity and follow-up duration), knowledge about hypertension, social support, and khat chewing and self-care practice (Supplementary File 1).…”
Section: Data Collection Tools and Measurementsmentioning
confidence: 99%
“…Dari 12 penelitian yang ditinjau beberapa faktor yang mempengaruhi self-care behavior pada klien dengan hipertensi di komunitas. Beberapa faktor yang mempengaruhi self-care behavior seperti faktor personal yang terdiri dari faktor sosio ekonomi, pendidikan, pengetahuan, peningkatan usia, dan persepsi terhadap penyakit (5,6,(11)(12)(13)(14) , self-efficacy yang merupakan kepercayaan seseorang dalam melakukan aktivitas tertentu, termasuk kepercayaan diri untuk melakukan aktivitas saat hambatan muncul (3,6,8,10,15) , dukungan keluarga yang merupakan upaya yang diberikan kepada anggota keluarga, baik moril maupun materiil, sehingga dengan dukungan itu seseorang merasa diperhatikan, mendapat saran, atau kesan yang menyenangkan pada dirinya (3,10,11) , dan spiritualitas yang merupakan pengalaman manusia secara umum dari suatu pengertian akan makna, tujuan dan moralitas (6) .…”
Section: Gambar 1 Diagram Flow Dan Pemilihan Artikelunclassified
“…Self-efficacy memberikan kontribusi terhadap pemahaman yang lebih baik dalam proses perubahan perilaku kesehatan sehingga sangat penting untuk meningkatkan perilaku perawatan diri pada klien hipertensi (8,15) . Seseorang dengan self-efficacy yang tinggi akan menganggap bahwa dirinya mampu menggunakan kemampuan untuk mencapai suatu hasil yang baik sesuai dengan apa yang diharapkan.…”
Section: Pembahasanunclassified
See 1 more Smart Citation